2019
DOI: 10.21608/asnj.2019.58161
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life among the Elderly patient with Urinary Incontinence: a Hospital Based Study at Assiut Governorate ,Egypt

Abstract: Background: Urinary incontinence had adverse effects on quality of life among elderly subjects through both physical and psychosocial consequences and a significant impact on physical health and daily functioning. Study Aim: assess the quality of life among elderly patient with urinary incontinence. Subject & methods: A descriptive research design was used. the study was conducted in urology outpatient at Assiut university and El Eman general hospital. The total sample size was 395 elderly. Two tools were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
2
1
1
Order By: Relevance
“…Concerning to occupation of the studied women, approximately two thirds of women were housewives. [21] is congruent with such result, who mentioned that around two thirds of studied patients were housewives. [22] were mismatching with the results of the current study they reported that more than half of the studied sample were working.…”
Section: The Discussion Covers the Main Results Finding As Followsupporting
confidence: 85%
See 2 more Smart Citations
“…Concerning to occupation of the studied women, approximately two thirds of women were housewives. [21] is congruent with such result, who mentioned that around two thirds of studied patients were housewives. [22] were mismatching with the results of the current study they reported that more than half of the studied sample were working.…”
Section: The Discussion Covers the Main Results Finding As Followsupporting
confidence: 85%
“…In relation to medications that may affect urination frequency among the studied sample as antidepressant or anticholinergic drugs, the present study revealed only one fifth of the studied women were took these medications. [21] were inconsistent with the current study they reported that more than two thirds of their studied sample took these medications.…”
Section: As Regarding To the Medical And Urological Data Of The Studi...contrasting
confidence: 95%
See 1 more Smart Citation
“…This might be justified by a finding revealed by a study in Assuit by Shaker et al, 42 who have found a statistically significant relationship between the educational status of elderly participants and their knowledge level ( P < .001); this may explain that well‐educated elderly individuals have good awareness and health information regarding their disease, including UI. This conforms to the results reported by Kessler et al, 43 who have reported that schooling years of elderly participants and their knowledge level are significantly related ( P = .002).…”
Section: Discussionmentioning
confidence: 94%